Effective Microorganisms 4 (EM-4) Application in The Process of Making Compost from Household Organic Waste to Increase Skills of PKK Members - Tabitha Sri Hartati Wulandari; Supiana Dian Nurtjahyani; Dede Nuraida; Christina Innocenti Tumiar Panggabean; Sukisno Sukisno (Universitas Lambung Mangkurat, 2024)
Handling the problem of household waste is getting more complicated by the day. Some people do not have a new perspective on dealing with waste. For this reason, serious handling is needed when utilizing household waste as a resource. Household waste is the largest contributor to creating organic waste, so to turn organic waste into resources, it is necessary to work on piles of organic waste from household waste by utilizing waste in compost. The benefits of compost are many in terms of fertilizing plants, so through community service, training activities for making compost with EM 4 were carried out for Baturetno PKK members, where 35 participants attended the training. The aim is to train PKK members skills in handling household organic waste by giving them EM4. In this activity, the methods used were socialization, training, and monitoring. In the training, a questionnaire was distributed to determine the participants' insight and response to the activity. The results of the questionnaire show that there is an increase in understanding and skills as seen from the average answer